2016
DOI: 10.1002/phar.1833
|View full text |Cite
|
Sign up to set email alerts
|

Value of a Community‐Based Medication Management Review Service in Jordan: A Prospective Randomized Controlled Study

Abstract: The MMR service resulted in a significantly lower number of TRPs and significantly improved clinical outcomes, and it was highly accepted by the physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 29 publications
(72 reference statements)
5
58
0
Order By: Relevance
“…This study showed no significant improvements in the quality of life of participants. Such results were not surprising, as previous studies, also conducted over 3 months, showed no quality of life improvements as an attribute to the service delivered . This could be due to insufficient time allowed to measure changes in quality of life.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study showed no significant improvements in the quality of life of participants. Such results were not surprising, as previous studies, also conducted over 3 months, showed no quality of life improvements as an attribute to the service delivered . This could be due to insufficient time allowed to measure changes in quality of life.…”
Section: Discussionsupporting
confidence: 56%
“… Paired‐sample t ‐test. Score of adherence (of 4, the lower the score, the better the adherence); score of self‐care activities (score of 42, the higher the score, the better the self‐care activities); score of quality of life (score of 1, the higher the score, the better the quality of life). …”
Section: Resultsmentioning
confidence: 99%
“…based on the scale developed previously by Morisky et al . The questionnaire has been applied effectively in previous similar studies . The questionnaire is composed of five items asking patients how often during the last month they forgot to take their medication, skipped their medication, stopped their medication when they felt better, stopped their medication when they felt worse or stopped their medication when they experienced a side effect.…”
Section: Methodsmentioning
confidence: 99%
“…In ambulatory care, the economic burden arising from healthcare resource consumption associated with TRPs has been estimated to be over $177 billion dollars in the US, with potentially preventable hospital admissions due to TRPs costing more than €94 million in the Netherlands . Identifying and preventing TRPs can help patients achieve their therapy goals and reach better possible health outcomes, better quality of life, less hospital admissions and better health economic status …”
Section: Introductionmentioning
confidence: 99%
“…Hence, pharmacy practice has grown from the traditional dispensing only duties to now being more patient‐centred based . Pharmacy practice research in the developing countries, such as Jordan, is also paving the way towards patient‐centred care …”
Section: Introductionmentioning
confidence: 99%